Philip J. Fisk, Jonathan Edwards’s Turn from the Classic-Reformed Tradition of Freedom of the Will - Schweitzer, Cameron (Jonathan Edwards studies, 2018)
This work will surely help to place Fisk among the well-respected authors in the philosophical studies of Northampton’s Pastor, among the likes of Oliver Crisp and Sang Hyun Lee. Fisk makes a unique contribution to this ongoing dialogue by showing the extent to which Edwards’s views on the subject situate him with respect to what our author labels the "Classic-Reformed tradition."